THRIVE Prevent Postoperative Hypoxemia in Elderly Patients Undergoing Laparoscopic Surgery in PACU: A Randomized Controlled Clinical Trial - Chen X; Gu K; Yang Y; Zhou B; Mo Y; Tu Y (Journal of Multidisciplinary Healthcare)
Xingxing Chen,1 Kang Gu,2 Yunqing Yang,2 Bingbing Zhou,1 Yunchang Mo,3 Yingying Tu1 1Department of Nursing, The First Affiliated Hospital of Wenzhou Medical University, WenZhou, ZheJiang, 325000, People’s Republic of China; 2Wenzhou Medical University, WenZhou, ZheJiang, 325000, People’s Republic of China; 3Department of Anesthesiology, The First Affiliated Hospital of Wenzhou Medical University, WenZhou, ZheJiang, 325000, People’s Republic of ChinaCorrespondence: Yunchang Mo, Email myc1104@wmuedu.cn Yingying Tu, Email tuyingying@wzhospital.cnBackground: Postoperative hypoxemia frequently occurs in elderly individuals undergoing laparoscopic procedures, often leading to severe consequences and prolonged stays in the post-anesthesia care unit (PACU). Conventional oxygen therapy methods are not entirely effective in preventing hypoxemia. Transnasal Humidified Rapid Insufflation Ventilatory Exchange (THRIVE) delivers high-flow oxygen at rates up to 60 L/min, potentially enhancing respiratory function and tolerance to hypoxia.Objective: To assess the effectiveness, safety, and patient tolerance of THRIVE in the early prevention of postoperative hypoxemia in elderly patients following laparoscopic surgery with general anesthesia.Methods: This prospective, multicenter, randomized controlled trial enrolled 200 elderly patients undergoing laparoscopic surgery who were safely extubated after general anesthesia. Participants were randomly allocated to receive either conventional nasal cannula oxygen therapy or THRIVE. Between January 2023 and December 2023, cases were recruited from three participating centers. The main outcome measured was the occurrence of hypoxemia in the PACU. Secondary outcomes encompassed lung ultrasound scores after oxygen therapy, frequency of jaw lifting, reintubation rate, adverse events, and subjective patient comfort.Results: The incidence of hypoxemia was significantly lower in the THRIVE group compared to the standard oxygen therapy group (0% vs 29.2%; χ² = 35.245; P < 0.001). The need for jaw lifting was also significantly reduced in the THRIVE group (5.1% vs 29.2%; P = 0.019). Moreover, patients receiving THRIVE demonstrated better lung aeration, as indicated by improved lung ultrasound scores (z = 3.016; P = 0.003), and reported significantly higher comfort levels in the PACU (z = 3.141; P = 0.002).Conclusion: THRIVE is an effective strategy for reducing postoperative hypoxemia in elderly individuals undergoing laparoscopic procedures with general anesthesia. It facilitates pulmonary function recovery, enhances patient comfort, and may serve as a valuable intervention in the PACU setting.Keywords: THRIVE, laparoscopic surgery, elderly patients, hypoxemia